A study on Filipino investors and their intention to invest in mutual funds in the Philippines - Gana, Jaan Alexander Lacap (Animo Repository, 2022)
The Philippine mutual funds industry has been around since the 1950s. However, its history has tainted the perception of Philippine investors towards it. Poor management of these funds in its early years led to bankruptcy of companies, collapse of the Philippine stock market, and the like. Some studies about mutual funds industries in neighboring Asian countries have suggested that fund managers are not implementing enough strategic investment plans to satisfy investors. Specifically, a study in India concluded that investors prefer to invest in gold and real estate markets (Kale & Panchapagesan, 2012). Recently, it has not been fully understood as to how Filipino investors view mutual funds as an investment opportunity and whether certain factors affect their decision to invest into it. The lack of knowledge on this type of investment vehicle is evident within a lot of areas in the country, and even about the general idea of investing. The research was conducted for the benefit of current and future Philippine investors, mutual funds companies in the country, as well as the researchers themselves. The study made use of a quantitative approach and was conducted using descriptive and explanatory research designs. Data was collected through a survey questionnaire to 90 active mutual fund investors and 90 non-active mutual fund investors, giving the study a total of 180 respondents using the convenience sampling method. The study was conducted during July-September 2022. Several statistical tests and models were utilized in order to analyze the gathered data. These include the Cronbach’s Alpha, Kruskal-Wallis Test, Ordinal Regression Equation, Pearson’s Goodness of Fit, and the Chi-square distribution. Major findings show that 62.4% of respondents are moderately familiar to very familiar with mutual funds, the majority of respondents are considered to be moderately aggressive and that growing their capital is their top reason for investing. Data also shows that the respondents are not exactly very unsatisfied with the returns they are getting, but they are also not very satisfied with the outcome and that the majority of respondents intend to continue or start investing in mutual funds. With this, it is concluded that investors are more likely to continue or start investing in mutual funds the more they are comfortable with risk. They are also more likely to continue or start investing in mutual funds if they are satisfied with the portfolio returns. Based on the Kruskal Wallis testing, there is an impact of familiarity on an investor’s intention to invest in mutual funds (contradicts Sashikala & Chitramani’s study (2018)), although it is unclear whether it would strengthen or weaken their intention. The researchers recommend that there be more education about mutual funds so as to let people know more about this investment vehicle. It is also recommended that, for future research, make use of ANOVA Testing to determine relationships between some variables. It is also recommended for future research to analyze more the relationship between portfolio satisfaction and the intention to invest in mutual funds.